2016
DOI: 10.3892/or.2016.5215
|View full text |Cite
|
Sign up to set email alerts
|

Immediate early response protein 2 regulates hepatocellular carcinoma cell adhesion and motility via integrin β1-mediated signaling pathway

Abstract: Human immediate early response 2 (IER2) has been reported to function as a potential transcriptional factor or transcriptional co‑activator and seems to play a pivotal role in tumor cell motility and metastasis, however, its role and underlying mechanisms in hepatocellular carcinoma (HCC) remain unknown. Herein, we demonstrated that overexpression of IER2 in HCC cells increased cell adhesion to fibronectin, migration and invasion, whereas knockdown of IER2 displayed the opposite effects. In agreement with this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
25
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 33 publications
1
25
1
Order By: Relevance
“…Xu et al [26] reported that IER2 promotes the migration and invasion of hepatocellular carcinoma cell adhesion and motility. Xu et al [27] demonstrated that IER2 promotes the migration and invasion of hepatocellular carcinoma cells via regulating the activity of Rho GTPases. Moreover, Moriya et al [28] reported that ier2 mRNA was distributed in the telencephalon, midbrain and the hypothalamus.…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al [26] reported that IER2 promotes the migration and invasion of hepatocellular carcinoma cell adhesion and motility. Xu et al [27] demonstrated that IER2 promotes the migration and invasion of hepatocellular carcinoma cells via regulating the activity of Rho GTPases. Moreover, Moriya et al [28] reported that ier2 mRNA was distributed in the telencephalon, midbrain and the hypothalamus.…”
Section: Discussionmentioning
confidence: 99%
“…These networks highlighted the interconnectivity of genes that were differentially expressed at different stages of tendon healing and provided insight into the importance of these genes. For instance, integrins (ITGs) are transmembrane receptors that facilitate cell-ECM adhesion and have two main functions: attach the cell to the ECM and transduce signals from the ECM to the cell [43,44]. The biological functions of ITGs family are mainly associated with adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…aureus . Ier2 is an immediate early response gene, affecting cell adhesion and motility [52, 53]. Although it has some DNA binding ability [54], nothing is known regarding its involvement in immunity or host defense.…”
Section: Discussionmentioning
confidence: 99%